Implementation of The Disability Service Unit at SLBN Cinta Asih - Tasha Amalia Utami; Emay Mastiani (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to describe the implementation of the Disability Service Unit (ULD) at SLBN Cinta Asih, particularly in the context of remote areas. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving the ULD coordinator and education staff at the SLBN Cinta Asih Disability Service Unit. The results show that although not administratively labeled as a DSU, the Learning Activity Center (TKB) has functionally performed the role of a DSU through initial assessments, the development of individual learning plans, and support services. The main challenges faced include limited facilities, the absence of professionals such as psychologists or therapists, and low parental involvement. However, flexible teaching strategies, the use of contextual learning materials, and a family-oriented approach have proven effective in maintaining special education services in the area. This study highlights the importance of community-based ULDs in supporting inclusive education in areas that do not have full access to formal special education services.